Effect of Smear Clear and Conventional Root Canal Irrigants on Push-Out Bond Strength of Resilon/Epiphany System - Afkhami, Farzaneh; Sadegh, Mona; Sooratgar, Aidin; Montazeri, Elham (Iranian Endodontic Journal, 2018)
Introduction: The aim of the present study is to compare the effect of SmearClear and sodiumhypochlorite (NaOCl), chlorhexidine (CHX) and normal saline (NS) on the push-out bond strength of Resilon/Epiphany system to dentine. Methods and Materials: In this in vitro study; 48 single-rooted teeth were selected and decoronated from the CEJ. Then the specimens were divided into four groups (n=12). The roots were prepared by single length technique using MTwo rotary system. The final irrigations of the canals were done using 2% CHX, normal saline, 5.25% NaOCl or SmearClear. The canals were obturated by Resilon/Epiphany system. The teeth were cut perpendicular to their longitudinal axis and four 1-mm-thick sections were obtained from coronal and mid root regions. The push-out bond strength of Resilon/Epiphany system to dentin were calculated and bond failure patterns were assessed. The data were subjected to two-way analysis of variance and Tukey’s tests. Results: The highest bond strength values were reported for SmearClear and the lowest values for the NS solutions. The effects of irrigant type (P<0.05) and canal area (P<0.0001) on the bond strength of Resilon to dentin were significant (P<0.05). Higher bond strength values were obtained in the mid root areas compared to the coronal regions. In two-by-two comparisons, significant differences in bond strength were found between SmearClear and normal saline (P<0.05) while the other irrigants showed no significant differences (P>0.05). Conclusion: SmearClear solution was able to increase the push-out bond strength of Resilon to the dentin similar to other irrigants (NaOCl and CHX). Therefore, it can be used for the root canal irrigation and smear layer removal in the clinical situations. Keywords: Push-But Bond Strength; Resilon; Root Canal Irrigation; SmearClear; Smear Layer